2004
DOI: 10.1016/j.jvs.2003.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety and durability of redo carotid operation: an 11-year experience

Abstract: RCO for recurrent carotid stenosis can be performed safely with excellent protection from stroke and long-term durability. These data provide a standard against which the results of carotid stenting can be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…[7][8][9] This is largely due to the inherent risks in any open reintervention in a previously operated field, such as increased scar tissue, which can obscure tissue planes and make identification of anatomic structures and surgical landmarks more challenging. Reoperation can have morbidity and mortality rates as high as 8% to 20%, [13][14][15][16][17][18][19][20] although recent literature suggests that this is improving. 6,[21][22][23] O'Donnell et al reported on the results from a metaanalysis of six series that showed a 4.2% stroke rate and a 1% mortality rate for redo carotid surgery, and indicated that the incidence of cranial nerve injury in these patients averaged 8.5%.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] This is largely due to the inherent risks in any open reintervention in a previously operated field, such as increased scar tissue, which can obscure tissue planes and make identification of anatomic structures and surgical landmarks more challenging. Reoperation can have morbidity and mortality rates as high as 8% to 20%, [13][14][15][16][17][18][19][20] although recent literature suggests that this is improving. 6,[21][22][23] O'Donnell et al reported on the results from a metaanalysis of six series that showed a 4.2% stroke rate and a 1% mortality rate for redo carotid surgery, and indicated that the incidence of cranial nerve injury in these patients averaged 8.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity (including cranial nerve injury) and mortality rates of 8% to 20% after redo CEA have been reported [22][23][24] ; however, several other authorities have reported better results. [25][26][27][28][29][30] Carotid percutaneous transluminal angioplasty and stenting is increasing in popularity and has been advocated by some investigators as an alternative to reoperation for post-CEA carotid stenosis. [31][32][33][34][35][36][37][38] In a multicenter study of 358 CAS procedures, New et al 35 reported a 30-day stroke and death rate of 3.7% with a 3-year rate of freedom from all strokes of 96% (SE, 1%).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events reported in both groups are much less frequent than the accepted standard for this surgery [1][2][3][4] according to other retrospective studies from single series. 20,21,[24][25][26][27][28][29][30] In particular, two postoperative deaths were due to cardiac complications, and no lethal or major stroke was reported in the study or control group. These are in fact the main evaluation criteria being considered in major international studies comparing CEA with optimal medical therapies and more recently with CAS.…”
Section: Discussionmentioning
confidence: 86%
“…In particular, patients with altered and unfavorable cervical anatomy due to previous carotid or oncologic surgery, cervical irradiation, abnormally high carotid bifurcation, and very short and inextensible neck, may pose significant technical challenges in terms of operating technique increasing the number of complications. 19 Several retrospective studies from surgical series have investigated the problem, 11,[19][20][21][22][23][24][25][26][27][28][29][30] but only considered the main early outcomes of postoperative mortality and major neurologic morbidity. Other periprocedural variables, minor complications, and late results, such as survival, late neurologic events, and restenoses disclosing perhaps directly or indirectly a higher procedural difficulty, have never been properly quantified, nor have safer and long lasting results been proved for patients with a hostile neck treated with CAS or medical therapy.…”
mentioning
confidence: 99%